Retrospective analysis of 14 cases of remote epidural hematoma as a postoperative complication after intracranial tumor resection. Issue 1 (December 2015) - Yu, Jinlu; Yang, Hongfa; Cui, Dayong; Li, Yunqian
Abstract Background The occurrence of remote epidural hematoma as a postoperative complication after intracranial tumor resection is rare. This study reviewed experiences treating these hematomas and speculated on the causes of this disease. This study reviewed the treatment experience of 14 such cases. Methods The 14 patients included 10 males and 4 females, with an age range of 19 to 65 years old. Six cases of tumors occurred in the sellar region, two cases in the lateral ventricle, one case in the fourth ventricle, one case in a cerebellar hemisphere, and four cases in other sites. Among them, five cases were complicated with supratentorial hydrocephalus. The tumors included five cases of meningioma tumors, two cases of pituitary adenomas, three cases of ependymomas, two cases of craniopharyngiomas, one case of astrocytoma, and one case of tuberculosis tumor. For the cases complicated with hydrocephalus, ventricular drainage was provided if needed, and the tumor resection was then performed, with close observation for postoperative changes. If neurological symptoms and disturbance of consciousness occurred, computed tomography (CT) examination was immediately performed. If a remote epidural hematoma was found, the hematoma was evacuated by craniotomy. The patients were followed up after surgery. In the five cases complicated with hydrocephalus, ventricular drainage was first provided for three cases. Results All of the 14 cases underwent total tumor resection, and postoperative remote epidural hematoma occurred in all cases, including eight cases on the ipsilateral side and adjacent to the supratentorial operative field; two cases occurred on the contralateral side; two cases occurred on bilateral sides; and two cases occurred in distant areas (with infratentorial surgery, the hematoma occurred on the supratentorial area). Postoperative remote epidural hematoma usually occurred 0.5–5 h after the tumor resection, when the tentorial hernia had already occurred. Following tumor resection and epidural hematoma evacuation, 13 patients were discharged with good recovery, and one patient died. Conclusions The reduced intracranial pressure due to the intracranial tumor resection may be the cause of this hematoma. This type of epidural hematoma is acute and often occurs before hernia. Thus, the risk of remote epidural hematoma after intracranial tumor resection needs to be made known. Aggressive hematoma evacuation can often result in satisfactory outcomes for patients.